Strengthening Community Literacy Culture and Implementing Irrigation Systems for Home-Based Medicinal Plants in ‘Aisyiyah Gegerbitung - Fenty Sukmawaty; Yuni Sri Wahyuni; Wanda Mahaputri (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
This research aims to strengthen the community's literacy culture while improving technical skills in the use of home plant medicines through the application of irrigation techniques in accordance with environmental conditions, especially in the 'Aisyiyah Gegerbitung Community, Sukabumi Regency. The focus of the research is directed at strengthening the cultural literacy of home plant medicine through the use of ancient Sundanese manuscripts as a source of traditional knowledge, as well as the application of appropriate technology in the form of simple drip irrigation to overcome limited air availability. The integration between cultural literacy and simple technology is seen as a contextual and sustainable community empowerment strategy. The research method uses a descriptive-qualitative approach with a participatory-based community service design. Partner communities are actively involved in all stages of activities, starting from problem identification, program planning, implementation of literacy activities and technical training, to evaluation of results. Data was collected through participatory observation, group discussions, and reflection with the community. The results of the study show that strengthening cultural literacy based on ancient Sundanese manuscripts increases public understanding, appreciative attitudes, and confidence in the knowledge of home medicinal plants. The application of the drip technique has been proven to increase the efficiency of water use and the success of medicinal plant care in the yard of the house. The integration of these two approaches contributes to increasing family health independence, strengthening the role of women as cultural preservation agents, and the formation of more sustainable resource utilization practices.